Transformation of Indian automobile industry through inter-organization IT initiative : AutoDX (A) - Verma, Sanjay (London : Indian Institute of Management, Ahmedabad, 2018)
The case centres on the 2015 common data exchange, an initiative for all automobile manufactures in India to share data. Part A of the case series examines the practicality and difficulty of implementing such a system and the potential benefits.
Originally Published InVerma, S. (2018). Transformation of Indian Automobile Industry Through Inter-Organization IT Initiative: AutoDX (A). IIMA/IS0135(A). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic data interchange -- India -- Case studies; Automobile industry and trade -- India -- Case studies